The ability of Zea mays ears (Young Corn) powder in enhancing nutritional composition and changing textural properties and sensory acceptability of yeast bread - Lim, J. Y.; Wan Rosli, W. I. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
Consumption of dietary fibre-rich food has been associated with various beneficial physiological properties and health effects. Presently, different types of natural fibre-rich ingredients are added into variety of bakery-based products to improve it fibre content for health promotional purposes. However, majority of these products are frequently added with imported dietary fibre ingredients. In the present study, bread samples were prepared with Zea mays ear (young corn) powder at the levels of either 2%, 4% or 6%. The bread samples were analyzed for nutritional composition, textural properties and sensory acceptance. Addition of young corn powder (YCP) at the level of 6% increases total dietary fibre (from 3.48% to 5.26%), moisture (from 25.64% to 26.55%), fat (from 4.35% to 4.61%) and protein content (from 9.13% to 9.51%) significantly. However, with the increasing of YCP levels in the bread, the carbohydrate content was decreased significantly (from 59.93% to 58.34%) while the ash content (from 0.95% to 0.99%) was not significantly affected. Results of texture profile analysis indicated that addition of YCP up to 6% not significantly affected the springiness (1.01-1.00) but significantly decreased cohesiveness (0.95-0.82). However, the addition of YCP up to 6% has increased hardness (0.18kg-0.57kg), gumminess (0.17kg-0.47kg) and chewiness (0.18kg-0.47kg) attributes of bread samples. On the other result, the sensory evaluation shows that the flavour score was not significantly affected by addition of YCP up to 4% (4.82-4.52) while the tenderness (4.53-4.42), elasticity (4.75-4.58), aroma (4.40-4.47), colour (4.93-4.55) and overall acceptance (4.80-4.35) scores were not significant affected up to 6%. In summary, breads with 4% addition of YCP were considered to be acceptable and potentially used in improving nutritional composition without changing sensory score.